2021
DOI: 10.1039/d1sm01063h
|View full text |Cite
|
Sign up to set email alerts
|

The C36 Laves phase in diblock polymer melts

Abstract: The C14 and C15 Laves phases form as micelle packing structures in many types of soft matter, but the related C36 phase, which consists of alternating C14-type and C15-type layers,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
3
5
0
Order By: Relevance
“…At the beginning, we just considered the similar candidate phases as those considered in the previous work by Liu et al, , including the BCC, C14, C15, σ, A15, and hexagonal cylinder (C 6 ) phases (Figure ). Though there is another Laves phase named as C36, Magruder, and Dorfman have verified that the C36 phase cannot be stable in neat AB or AB/A blending systems . In our SCFT calculations, we have confirmed that the stability of C36 is intermediate between C14 and C15, and thus, it does not have a stable region in the AB/AB blending system.…”
Section: Resultssupporting
confidence: 50%
“…At the beginning, we just considered the similar candidate phases as those considered in the previous work by Liu et al, , including the BCC, C14, C15, σ, A15, and hexagonal cylinder (C 6 ) phases (Figure ). Though there is another Laves phase named as C36, Magruder, and Dorfman have verified that the C36 phase cannot be stable in neat AB or AB/A blending systems . In our SCFT calculations, we have confirmed that the stability of C36 is intermediate between C14 and C15, and thus, it does not have a stable region in the AB/AB blending system.…”
Section: Resultssupporting
confidence: 50%
“…These bcc phases are composed of micelles of the majority component at the lattice sites, with the minority component at the interstitial sites. The choice of C15 (vs C14) for the present purposes is arbitrary as these two phases are nearly degenerate in free energy as shown in prior work, 17,18,32,59 and that proves to be the case here, too (Figure S10).…”
Section: ■ Resultsmentioning
confidence: 65%
“…This near-degeneracy between C14 and C15 is expected from prior work. 17,18,32,59 Ultimately, distinguishing between these two very similar Laves phase particle packings is of little relevance in practice because fluctuation effects 12 and uncertainties in the experimental data (polydispersity, precision in measuring the degree of polymerization, mapping multiple χ parameters to experiments 64,65 ) make it challenging to translate such subtle SCFT predictions into experimental realizations. For this reason, we will simply refer to the stable state as the "Laves" phase in what follows, with the understanding that SCFT predicts C14 but it is very plausible that C15 could be realized in practice.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations